KOMPENSASI DAN MOTIVASI KERJA PENGARUHNYA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Muhamad Rifa'i; Rosalia Sela; Rr Nugraheni Suci Sayekti (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2021)
This study empirically tested the effect of compensation and work motivation on employee performance directly or indirectly mediated by job satisfaction as intervening variables. This research uses a quantitative approach. Data is primary data collected using questionnaires. The data is analyzed using a path analysis model using the Smart-PLS program. The results of the study showed that partial compensation has a significant and positive influence on job satisfaction Work motivation has a significant positive influence on job satisfaction Compensation has no influence on employee performance. Work motivation has no effect on employee performance. Job satisfaction has a significant and positive influence on employee performance. Compensation has an insorant and positive effect on employee performance through job satisfaction. Work motivation has a significant and positive effect on employee performance that is mediated by job satisfaction.